2012
DOI: 10.1590/s0100-204x2012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Análise dialélica de linhagens de milho com ênfase na resistência a doenças foliares

Abstract: Resumo -O objetivo deste trabalho foi identificar o tipo de ação gênica predominante para resistência a Exserohilum turcicum, Phaeosphaeria maydis, Physopella zeae e Puccinia polysora, e determinar o potencial genético de linhagens endogâmicas de milho (Zea mays) para a obtenção de híbridos com elevado desempenho agronômico e resistência a doenças foliares. Os 41 híbridos F 1 , provenientes de cruzamentos dialélicos entre dez linhagens endogâmicas, e as testemunhas P3069, P30F90, BG7060, Balu761 e Dow2A120 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
1
12
1
8
Order By: Relevance
“…Em geral, os efeitos gênicos não aditivos predominam quanto à produtividade (Hallauer & Miranda Filho, 1985;Nihei & Ferreira, 2012) e eficiência de utilização de P em milho (Fritsche-Neto et al, 2010;DoVale & Fritsche-Neto, 2013;Mendes et al, 2014). Contudo, alguns dialelos indicam a predominância de efeitos aditivos quanto à produtividade, resistência a doenças e capacidade de expansão do milho-pipoca (Freitas Júnior et al, 2006;Scapim et al, 2006a), resistência à mancha-branca (Nihei & Ferreira, 2012), e mesmo quanto à eficiência de uso de P (Meirelles, 2013).…”
unclassified
See 1 more Smart Citation
“…Em geral, os efeitos gênicos não aditivos predominam quanto à produtividade (Hallauer & Miranda Filho, 1985;Nihei & Ferreira, 2012) e eficiência de utilização de P em milho (Fritsche-Neto et al, 2010;DoVale & Fritsche-Neto, 2013;Mendes et al, 2014). Contudo, alguns dialelos indicam a predominância de efeitos aditivos quanto à produtividade, resistência a doenças e capacidade de expansão do milho-pipoca (Freitas Júnior et al, 2006;Scapim et al, 2006a), resistência à mancha-branca (Nihei & Ferreira, 2012), e mesmo quanto à eficiência de uso de P (Meirelles, 2013).…”
unclassified
“…Contudo, alguns dialelos indicam a predominância de efeitos aditivos quanto à produtividade, resistência a doenças e capacidade de expansão do milho-pipoca (Freitas Júnior et al, 2006;Scapim et al, 2006a), resistência à mancha-branca (Nihei & Ferreira, 2012), e mesmo quanto à eficiência de uso de P (Meirelles, 2013).…”
unclassified
“…Therefore, it is advisable to note that the maximum incidence and severity indexes in this study were about 0 to 75% in leaves of the upper middle third of the plant with lesions (grades ranged from 1 to 5), allowing a representative discrimination of the resistance levels. This amplitude of severity was equal to or greater than the studies of northern leaf blight under natural infestations (Viera et al, 2009;Nihei and Ferreira, 2012). Analyzing the averages of the parents (Table 2), it can be observed that the parental 1 and 2 were highly contrasting, since they presented totally divergent average values for the disease in question.…”
Section: Genetic Inheritance Of Northern Leaf Blight Resistancementioning
confidence: 62%
“…The maize crop in Brazil began to face serious disease problems from the 1990s, both by increasing frequencies and by severe qualitative and quantitative damages to production (Nihei and Ferreira, 2012). This increase in the amount of diseases is highly related to changes in the production system of maize crop, such as expansion of the agricultural border, expansion of planting seasons (crop and winter crop), adoption of direct planting, increased use of irrigation systems, lack of crop rotation and use of susceptible materials (Silva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Results concerning the prominence of gene effects on resistance to E. turcicum in conventional corn have been controversial. Paterniani et al (2000) and Vivek et al (2010), for instance, found that the additive genes were the most important in the expression of resistance to E. turcicum; the opposite occurred in the study developed by Nihei and Ferreira (2012). These findings indicate that genetic control for this trait may vary across the different sources of resistance.…”
Section: Resultsmentioning
confidence: 93%